A Celtiberian tessera and some inscriptions on instrumentum from Graccurris (Alfaro, La Rioja) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper presents two new Celtiberian inscriptions, a tes-sera and a new graffito, and assesses two already known graffiti from Graccurris (Alfaro, La Rioja).
Keywords: Celtiberian tessera; Celtiberian epigraphy; Celtiberian language; Gracurris; Celtiberian graffito